2018
DOI: 10.3389/fonc.2018.00115
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Cranial Irradiation in Patients With Non-Small-Cell Lung Cancer: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: BackgroundWe systematically reviewed the literature for trials addressing the efficacy of prophylactic cranial irradiation (PCI) in patients with non-small-cell lung cancer (NSCLC) treated with a curative intent.MethodsRandomized controlled trials (RCT) comparing PCI to no PCI in patients with NSCLC treated with a curative intent were eligible for inclusion. We searched EMBASE, MEDLINE, PubMed, and CENTRAL between 1946 and July 2016. We also received continual search alerts from PubMed through September 2017. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 82 publications
1
15
0
Order By: Relevance
“…Second, in the aspect of systematic treatment, appropriate treatment lines of anticancer drugs can be moved forward for highrisk patients to prevent BM, especially in HER2-positive breast cancer, due to the excellent efficacy of novel targeted drugs. Third, in the aspect of local treatment, prophylactic cranial irradiation (PCI) is currently recommended for patients with small-cell lung cancer due to the significant rate of occult BM, resulting in reduced incidence of BM and improved survival outcomes (41)(42)(43). Although no guidelines recommended PCI for breast cancer to prevent BM currently, future randomized clinical trials of PCI for BM prevention might be undertaken in selected patients since high-risk groups can be identified by our nomogram.…”
Section: Discussionmentioning
confidence: 99%
“…Second, in the aspect of systematic treatment, appropriate treatment lines of anticancer drugs can be moved forward for highrisk patients to prevent BM, especially in HER2-positive breast cancer, due to the excellent efficacy of novel targeted drugs. Third, in the aspect of local treatment, prophylactic cranial irradiation (PCI) is currently recommended for patients with small-cell lung cancer due to the significant rate of occult BM, resulting in reduced incidence of BM and improved survival outcomes (41)(42)(43). Although no guidelines recommended PCI for breast cancer to prevent BM currently, future randomized clinical trials of PCI for BM prevention might be undertaken in selected patients since high-risk groups can be identified by our nomogram.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this is the most recent meta-analysis with all available updated data from randomized controlled trials regarding the role of PCI for NSCLC. Previously, four meta-analyses (21)(22)(23)(24) have been carried out to evaluate the efficacy of PCI for NSCLC with inconsistent results. Published reviews demonstrated the effect of PCI in the prevention of BM in NSCLC which are in line with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…However, with regard to effect of PCI on OS, previous reviews drew discordant conclusions. In the meta-analysis of Al Feghali and Lester (21,22), PCI failed to prolong survival for NSCLC while Xie et al (24) reported a detrimental effect on survival with PCI over observation. The meta-analysis by Xie et al (24) included the RCT of Pottgen et al (12), which was judged by our reviewers impossible to evaluate the effect of PCI on BM due to the study design that local treatment between the two arms was different.…”
Section: Discussionmentioning
confidence: 99%
“…Three randomized studies have looked at the role of PCI in unselected Stage III NSCLC patients in the modern era treated in a multi-institutional setting with all three having slower than expected accrual and showing variable benefits [23], [24], [25]. A systematic review and meta-analysis including the two older studies as well as four additional trials from an earlier era also suggested that PCI decreases the risk of developing BM without an improvement in OS [26]. None of these studies included follow-up brain imaging unless symptoms suggestive of BM were present.…”
Section: Discussionmentioning
confidence: 99%